(untitled) (The Review of Diabetic Studies, 2025)
Neonatal resuscitation in the field is a critical intervention performed by paramedics to improve early survival in newborns experiencing perinatal distress. This review explores the vital role of paramedics in neonatal resuscitation, focusing on the physiological basis of neonatal vulnerability, epidemiological data on out-of-hospital births, and the impact of early resuscitative efforts on survival outcomes. Neonatal physiology is characterized by the need for rapid establishment of effective ventilation and unique challenges related to airway anatomy, temperature regulation, and circulatory changes. Common causes of neonatal collapse in the field include respiratory depression, cardiac etiologies, hypothermia, birth trauma, asphyxia, and infection. Paramedic scope of practice in neonatal care is defined by legal frameworks, training, and certification standards such as the Neonatal Resuscitation Program (NRP). Prehospital neonatal resuscitation algorithms emphasize rapid assessment, airway management, positive pressure ventilation, chest compressions, and judicious use of oxygen and medications. Specialized equipment and technology, including neonatal-specific resuscitation kits, portable incubators, and telemedicine integration, are essential for effective neonatal care in the field. Paramedics face challenges related to limited equipment availability, skill maintenance, environmental constraints, communication, and coordination with hospital-based teams. Evidence supports the significant impact of paramedic interventions on reducing neonatal mortality and morbidity. Innovations such as portable neonatal ventilators, real-time teleconsultation, wearable thermal monitoring, AI decision support, and specialized neonatal paramedic teams hold promise for further improving neonatal survival in the prehospital setting.